MCP-1/CCR2 axis regulates M2 macrophage polarization and immunosuppression in mycobacterium tuberculosis - Zhao, Guizeng; Guo, Can; Li, Xiaoyang; Tan, Lei; Chen, Xueyang; Tian, Feng; Zhang, Lili; Wang, Xia; Cui, Junwei (Frontiers in Immunology, 2026)
BackgroundMycobacterium tuberculosis (MTB) evades host immunity and maintains chronic infection, in part by reprogramming macrophage function. The chemokine MCP-1 and its receptor CCR2 play a key role in attracting monocytes and immunological modulation, but their exact involvement in MTB pathogenesis is unknown.MethodsUsing the H37Ra-infected mouse model, the expression of MTB virulence marker ESAT-6 and autophagy marker Beclin-1 was assessed. Transcriptome analysis was performed to identify CCR2-related gene expression changes and enriched pathways. In addition, the effects of CCR2 antagonists and MCP-1 knockdown on macrophage apoptosis, polarization, cytokine production, and immunosuppressive signaling were assessed using Quantitative real-time PCR, ELISA, flow cytometry, immunohistochemistry, immunofluorescence, and western blot.ResultsCCR2 inhibition reduced ESAT-6 expression and restored Beclin-1 levels in lung tissue, alleviating inflammation and injury during late-stage infection. Transcriptomic profiling revealed that H37Ra infection activated CCR2-dependent genes involved in immune response and apoptosis, including Trim30, Fas, and PD-1, which were reversed by CCR2 antagonists. At the cellular level, H37Ra upregulated MCP-1 expression, promoting M2 polarization. MCP-1 Knockdown enhanced macrophage apoptosis, reversed M2 polarization, and suppressed immunosuppressive signaling. Additionally, MCP-1 knockdown increased TNF-α and IFN-γ levels, reduced TGF-β and IL-10 secretion, and oppositely regulated ESAT-6 and Beclin-1 expression.ConclusionThe MCP-1/CCR2 axis promotes M2-type macrophage polarization, suppresses apoptosis, and enhances immunosuppressive signaling in the context of H37Ra infection. Targeting CCR2/MCP-1 may provide a promising strategy to reverse immune evasion and restore host defense mechanisms during MTB infection.